Dual manipulation of light and shape based on nanoparticle-induced shape memory composites. Issue 14 (29th March 2023) - Liu, Mingxia; Fan, Mingyang; Zhu, Shu; Liu, Weiping; Yang, Lili; Ge, Dengteng
Abstract : A versatile membrane with integrated visible transparency and shape manipulation is reported based on the thermo-irritated shape memory polymers and doped nonclose-packing nanoparticles (NPs). Abstract : In nature, many mysterious creatures are capable of defense and courtship via mimicry or color change. However, developing smart materials with the integration of conformation and color/transparency changes is an intriguing but challenging task. Herein, we report a versatile membrane with integrated visible transparency and shape manipulation. This membrane consists of thermo-irritated shape memory polymers and doped nonclose-packing nanoparticles (NPs). A reversible transparency change with shape deformation (from 63.7% to 2.1%) is exhibited due to the light scattering from internal cavitation between the NPs and polymers. Meanwhile, the shape of the film can be programmed and reversibly actuated via thermal-control bidirectional actuation from the semi-crystalline structure of poly(ethylene- co -vinyl)acetate (EVA). The complex film also shows excellent stability of light and shape modulation after the first cycle. The programmable reconfiguration and transparency-changing of this smart film highlight its great potential in temperature recording, light/thermal management, anti-counterfeiting and camouflage.